Are programmed cell death 1 gene polymorphisms correlated with susceptibility to rheumatoid arthritis?: A meta-analysis. Issue 35 (September 2017) - Zou, Yuming; Zhang, Ziteng; Liu, Yangang; Liu, Denghui; Xu, Weidong
Abstract: Background: Several studies investigated the relationship between programmed cell death 1 ( PDCD1 ) gene polymorphisms and rheumatoid arthritis (RA) risk, but the results were controversial. To explore whether PDCD1 gene polymorphisms have an effect on RA risk, we conducted this meta-analysis to investigate the relationships between PDCD1 polymorphisms (rs36084323 [PD-1.1 G/A], rs11568821 [PD-1.3 G/A] and rs2227981 [PD-1.5 C/T]) and RA risk under 4 genetic models. Methods: PubMed, EMBASE, Web of Science, Cochrane Library China National Knowledge Infrastructure (CNKI), and Chinese Biomedical Literature Database (CBLM) were systematically searched for all eligible case-control studies. The last search was updated on September 10, 2016. Studies were accessed using Newcastle-Ottawa Scale case control study (NOS), and the combined effect size was calculated using STATA software, version 12.0. The pooled odds ratio (OR) with 95% confidence interval (CI) was calculated to assess the association. Heterogeneity analysis and subgroup analysis were also performed. Sensitivity analysis and publication bias were also performed if necessary. Results: This meta-analysis included 6 studies. The result demonstrated null association between rs36084323 (PD-1.1 G/A) polymorphism and RA susceptibility in all 4 genetic models. With regard to rs11568821 (PD-1.3 G/A), statistically significant association with RA risk was observed under allele model in Caucasians (allele model A vs G, OR = 1.19, 95% CI = 1.03–1.41). There was no significant association between rs2227981 (PD-1.5 C/T) polymorphism and RA risk. Conclusion: The present study suggests that mutant A allele in rs11568821 (PD-1.3 G/A) might increase the susceptibility to RA in Caucasians.